Prevalence of allergic fungal sinusitis among patients with nasal polyposis - Rahim Dhanani; Shayan Khalid Ghaloo; Basit Salam; Hamdan Ahmed Pasha; Farah Hafiz Yousuf; Mubasher Ikram (Journal of the Pakistan Medical Association, 2021)
Objective: The objectives of the study were to determine the frequency of AFS among patients with nasal polyps and to compare the Lund-Mackay scores of patients with and without AFS. Methods: The study was carried out at a tertiary health care center of Karachi, Pakistan from December 2016 to November 2018, after taking ethical approval. Total of 114 patients with sinonasal polyposis undergoing surgery were included. Patients were categorized as case of AFS when histopathology showed allergic mucin with fungal hyphae and culture was positive for fungal growth. Lund-Mackay scoring based on CT PNS of each patient was done and mean scores of AFS and non AFS patients were compared. Results: Mean age of 114 participants was 37.3 ± 15.3 years. 61 (53.5%) of them were males. 27 (23.7%) patients met the AFS criteria. 19 (16.7%) patients were asthmatic and a significant relationship was found between asthma and AFS (P = 0.03). The mean Lund-Mackay score was 13.2 for non AFS and 18.8 for AFS patients (P = <0.01). Recurrence was seen in 11 (9.6%) cases. Conclusion: The frequency of AFS in patients with nasal polyps was 23.7% and the patients with AFS showed significantly higher mean Lund-Mackay score compared to non AFS patients. Continuous....